Medical pluralism and livestock health: ethnomedical and biomedical veterinary knowledge among East African agropastoralists. Issue 1 (December 2017) - Caudell, Mark; Quinlan, Marsha; Quinlan, Robert; Call, Douglas
Abstract Background Human and animal health are deeply intertwined in livestock dependent areas. Livestock health contributes to food security and can influence human health through the transmission of zoonotic diseases. In low-income countries diagnosis and treatment of livestock diseases is often carried out by household members who draw upon both ethnoveterinary medicine (EVM) and contemporary veterinary biomedicine (VB). Expertise in these knowledge bases, along with their coexistence, informs treatment and thus ultimately impacts animal and human health. The aim of the current study was to determine how socio-cultural and ecological differences within and between two livestock-keeping populations, the Maasai of northern Tanzania and Koore of southwest Ethiopia, impact expertise in EVM and VB and coexistence of the two knowledge bases. Methods An ethnoveterinary research project was conducted to examine dimensions of EVM and VB knowledge among the Maasai (N  = 142 households) and the Koore (N  = 100). Cultural consensus methods were used to quantify expertise and the level of agreement on EVM and VB knowledge. Ordinary least squares regression was used to model patterns of expertise and consensus across groups and to examine associations between knowledge and demographic/sociocultural attributes. Results Maasai and Koore informants displayed high consensus on EVM but only the Koore displayed consensus on VB knowledge. EVM expertise in the Koore varied across gender, herd size, and level of VB expertise. EVM expertise was highest in the Maasai but was only associated with age. The only factor associated with VB expertise was EVM expertise in the Koore. Conclusions Variation in consensus and the correlates of expertise across the Maassi and the Koore are likely related to differences in the cultural transmission of EVM and VB knowledge. Transmission dynamics are established by the integration of livestock within the socioecological systems of the Maasai and Koore and culture historical experiences with livestock disease. Consideration of the nature and coexistence of EVM and VB provides insight into the capacity of groups to cope with disease outbreaks, pharmaceutical use patterns, and the development of community health interventions.